Faktor yang Mempengaruhi Orang Tua Memberikan Gadget pada Anak - Wardatus Sholihah; Allenidekania Allenidekania; Imami Nur Rachmawati (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the factors influencing parents to give children gadgets. This research method is a systematic review using several online databases, ProQuest, EBSCOhost, Scopus, and Google scholar. The results showed that 11 articles were reviewed and found three main themes: socio-economic status, knowledge, and parenting patterns related to giving gadgets to children. In conclusion, this article shows that giving gadgets to children is influenced by the family's socio-economic status, parenting patterns with permissive and authoritarian parenting styles, and parents' knowledge of gadget use. Keywords: Children, Gadgets, Knowledge, Parenting, Socio-Economic Family